My neighbor Totoro [videorecording (Blu-Ray + DVD)] - Miyazaki, Hayao, 1941-; Hewitt, Cindy Davis; Hewitt, Donald H.; Hisaishi, Jō, 1950-; Satō, Yoshiharu (1988)
After moving to the country to be near their ailing mother, two young sisters are befriended by a variety of mysterious creatures.